Fluid needs for training and competition in athletics - Shirreffs, S. M.; Casa, D. J.; Carter, R. (Journal of Sports Sciences, 2007)
The diverse nature of the athletic events, together with the varied training programmes and individuality of athletes taking part, inevitably means that fluid needs are highly variable - between athletes, perhaps between training and competition, and with differing environmental conditions and degree of training and heat acclimatization. There are limited data from athletics on all aspects of fluid balance, but wherever possible we have focused on this information to draw conclusions. When appropriate, euhydration will best be ensured by consuming 6-8 ml/kg body mass of a sodium-containing fluid, or sodium-free fluid together with food, about 2 h before exercise. The individual sweat responses are so variable that athletes should assess their own individual sweat losses to determine if these are likely to be a cause for concern. The volume of drink that is consumed should never be so much that an athlete gains mass over an event, unless perhaps there is evidence that they began in a hypohydrated state. This may be a particular concern in the field events and multi-event disciplines when competition can be spread over a number of hours and when there are significant rest periods between activities.